Influence of the strip-shaped air-out slits’ width in the fully mechanized working face under wallattached swirling ventilation condition - Li Yongjun; Wang Pengfei; Liu Ronghua; Han Han; Tan Xuanhao; Jiang Yidan (E3S Web of Conferences, 2019)
For the purpose of mastering the influence of the strip-shaped air-out slits’ width in the fully mechanized working face under wallattached swirling ventilation condition, By using fluent software, numerical simulation of airflow field and dust diffusion in fully mechanized working face under different strip-shaped air-out slits’ width conditions was carried out. The results show that the wall-attached swirling ventilation can effectively control the dust diffusion in the fully mechanized working face, improve the dust collecting effect of the bag precipitator fan, and reduce the particle mass concentration at the driver and the rear of the tunnel; Increasing the air volume of the strip-shaped airout slits can improve the control effect of the swirling air curtain on the dust, appropriate air volume can make the swirling air curtain control the dusty airflow and push it to the end of the heading surface to control, block and propel the dust; When the width of the strip-shaped air-out slits is 0.06 m, the dust collecting effect of the exhaust air cylinder on the dust and the effect of the wall-attached swirling on the plugging of the dust are best.